Framing the Fact of Extraordinary Events - Atmadi, Gayatri (UI Scholars Hub, 2019)
The very apprehensive fact of disease outbreaks of measles and malnutrition which led to dozens of children die in Asmat, Papua is mentioned as the extraordinary events (KLB) by the Ministry of Health Republic of Indonesia. The reports from journalists about the health disaster in Asmat deep concerns for the readers of the daily Kompas for several days. This research aims to find out how framing the news conducted by editor Kompas which acts as a good watchdog in overseeing the health disaster management in Asmat. By using social construction of mass media theory as the main thought, this research also uses theory of agenda setting and issues management. This type of research is qualitative with constructivism paradigm and research method is text analysis. In constructionist view, daily Kompas is seen as the construction agent of the news and the news published by Kompas is the result of construction of the reality. This study uses framing model analysis from Pan and Kosicki which includes four structures, namely: (1) Syntax, (2). Script, (3). Thematic,(4). Rhetorical. The results show that in framing the fact of extraordinary incident, Kompas already worked hard to gain qualified journalism so that can be a differentiation factor of trusted news in facing the challenge of sustainability mass media business.